Redefining social enterprise in the global world: study of China and India. Issue 7 (8th July 2019) - Oberoi, Roopinder; Cook, Ian G.; Halsall, Jamie P.; Snowden, Michael; Woodock, Pete
Abstract : Purpose: Social enterprise plays a pivotal role in helping people and communities. Since the global financial crisis of 2008, there has been an upsurge of social enterprise within a local, national and global context. The purpose of this paper is to explore the debates and issues presented by social enterprise in a very complex globalized world. Design/methodology/approach: In this paper, the authors apply two geographical case studies: China and India. The purpose for selecting both China and India is their increasing economic super power on the global stage. It is argued that the concept of social enterprise within the geographical context of China and India is significant to their individual economies. Findings: The concept of social enterprise within the geographical context of China and India is significant to their individual economies and as explored within the notion of "think global, act local" the conceptual debates of place, space and time enables people to take positive action and enable the development of healthy communities. Originality/value: This paper contributes to the discussion around the definition of the nature of social enterprise and gives concrete examples of the contextually specific nature of the term.